Kajian Faktor-Faktor yang Mempengaruhi Minat Wisatawan Mengunjungi Objek Wisata Pantai Nirun Kabupaten Maluku Tenggara - Salma Madubun; Melissa Justine Renjaan; Rahma Gusmawati Tammu (Universitas Kristen Indonesia Toraja, 2025)
Nirun Beach is located in Ohoi Elaar, Southeast Maluku Regency, and has become one of the prominent tourist destinations. This research aims to identify the factors affecting tourists’ interest in visiting Nirun Beach in Ohoi Elaar Ngursoin, Southeast Maluku Regency, and to determine the most dominant factor. The research method used is a quantitative method with a questionnaire instrument using a Likert scale, involving 100 tourist respondents. The research results show that the factors affecting tourists’ interest include economic factors (70%), environmental factors (84.75%), technology and social media (77.31%), accessibility and infrastructure (71.12%), and the interest in visiting (79%). Among these five factors, the environmental factor scored the highest, indicating that the beauty and sustainability of Nirun Beach’s nature are the main attraction for tourists. The conclusion of this study is that, although other factors such as the economy, accessibility, and infrastructure have an impact, the environmental aspect remains the dominant factor. The recommendations from this study are the need for improvements in facilities, accessibility, tourism promotion through social media, and involving the local community in tourism management to increase the appeal of Nirun Beach.